2022-RA-684-ESGO Factors affecting survival outcomes of patients with clear cell endometrial carcinoma. (20th October 2022) - Pergialiotis, Vasilios; Christodoulou, Theano; Prokopakis, Ioannis; Haidopoulos, Dimitrios; Rodolakis, Alexandros; Thomakos, Nikolaos
Abstract : Introduction/Background: Clear cell endometrial carcinoma comprises an aggressive subtype of endometrial cancer that is associated with poor survival outcomes compared to endometrioid carcinoma. It is encountered in less than 5 percent of cases with endometrial cancer.Biologically, it is associated with an increased propensity for lymphovascular invasion and intraperitoneal spread. The purpose of the present study is to identify patient and tumor characteristics that correlate with survival outcomes. Methodology: We conducted a retrospective chart review of endometrial cancer patients to evaluate survival outcomes and factors affecting survival in those with clear cell histological subtype. Stage of the disease, tumor maximal diameter, staging characteristics patient phenotype, smoking status and type of adjuvant therapy were considered as potential parameters that affected survival. Results: Sixty patients were identified with a median follow-up duration of 37 months (8–72). Early stage disease (stage I and II) was observed in 32 patients. Of those 26 patients experienced disease recurrence and 16 died during the follow-up period. Patients recurred within 15.5 months from initial treatment (95% CI 9.7 – 21.3 months). Death occured within a median follow-up of 31.2 months (95% CI 16.1 – 54.7 months). Disease stage (p<.001), patient age (p=.023) and use of adjuvant chemotherapy (p were independently associated with progression free survival, whereas only stage of the disease (p=.008) was independently associated with overall survival rates. Conclusion: Clear cell carcinoma is an aggressive form of cancer that is associated with increased relapse rates and a short interval to recurrence. Stage of the disease appears to be the most important determinant of progression free and overall survival rates. Cases treated with adjuvant chemotherapy appear to have improved chances of avoiding recurrences, however, its use does not seem to increase overall survival rates.